Exploring Anxiety in Individuals Aged 15-30: The Role of Academic and Professional Stressors and Evidence – Based Intervention. - Chatta, Vasundhra; Gupta, Mansi; Vikas, Vikas; Sarmah, Puja; Gopal; Shankar Tiwari, Shiv (Journal of Neonatal Surgery, 2025)
BACKGROUND: Anxiety is the normal reaction to stress (Cabrera, V. (2020)). According to the National Institute of Mental Health, approximately 31.9% of adolescents aged 13-18 and 25.8% of young adults aged 18-29 experience an anxiety at some point in their lives. This paper aims to investigate the specific academic, professional stressors contributing to anxiety in individuals aged 15-30, and to analyze the effectiveness of various evidence- based interventions. RESEARCH GAP: There are several key research gaps in the field of anxiety and its management. One major gap is the lack of personalized treatment approaches that take into account individual differences in genetics, environment, and psychological factors (Hofmann et al., 2012). Additionally, there is limited research on the long- term efficacy and safety of existing therapies, such as medications and cognitive behavioral therapy (CBT).There is gap in research focusing on understudied populations, such as children, the elderly, and minority groups, where anxiety manifests differently and may require tailored interventions. OBJECTIVE: (1) to determine the prevalence of anxiety for individuals aged 15- 30 (2) to determine academic and professional stressors contributing to anxiety (3) to determine the interventions related with anxiety. METHODS: This was a survey-based study conducted on individuals aged 15-30 years to find the prevalence of anxiety and its associations with interventions for treating. A questionnaire disseminated in the form of a survey on mobiles to individuals aged 15–30 years living in different states across India. RESULTS: This study highlights about 48.6% have moderate anxiety, 35.7% have mild anxiety and 15.7% have severe anxiety. On the other hand, 12.9% are extremely anxious for their placements and just 2.9% are less anxious about their jobs. There is various coping strategy to manage anxiety, which includes talking to family and friends, meditation, professional help, listening to music, doing exercises, sleeping and main try to face the problems. CONCLUSION: Anxiety among individuals aged 15 -30 is a growing concern, driven by a range of academic and professional stressors. Effective interventions, such as cognitive- behavioral therapy, mindfulness practices and peer support system, offer significant relief and help individuals build resilience against stress..